Development as security, the assault on poverty and structural adjustment: the World Bank during the McNamara years (1968-1981) - Pereira, João Márcio Mendes (Revista de História, 2011)
The article analyzes the World Bank’s action during Robert McNamara’s presidency, situating it in the context of the Cold War and the conduct of American foreign policy, which was increasingly subordinated to interference by the United States Congress. It discusses the reasons and means through which the World Bank conducted, since 1968, its “assault on poverty” and makes a general interpretation of this experience. Finally, it deals with the launching of structural adjustment loans in 1980 under the radical changes in the international political economy which occurred between 1979 and 1981.